Clinical trials studies of plant extracts with anti-inflammatory activity - Eloísa Portugal Barros Silva Soares de Souza, Robson Xavier Faria, Leandro Machado Rocha (Journal of Applied Pharmaceutical Science, 2016)
The therapeutic potential of medicinal plants has been studied and evaluated in scientific circles. The anti-inflammatory activity was established as being of great importance, by considering the number of diseases that it involves, the high investment of industries and adverse effects of patients. There is no doubt that this is a promising way in many cases, due to the diversity of structures and substances contained in plants. But although many of the plant extracts have been evaluated against activities in vitro and in vivo, not all reached the stage of clinical trials in humans in order to reach someday the pharmaceutical market. Some phytochemical studies also seek a biologically active isolated molecule. Our purpose with this study is to show the plants whose anti-inflammatory activity has already been studied in pre-clinical trials and that where conducted clinical studies in humans, providing a new observation perspective of herbal products, regardless of a search for a synthesizable isolated substance, with the knowledge of the activity of one or more extracts as a whole.
Keywords: Plant extracts, anti-inflammatory, clinical trials.